Museum and monument : a study on the architectural features of heritage building for museum (with reference to preventive conservation) / Muhammad Ilmam Tharazi - Tharazi, Muhammad Ilmam (2011)
This research is about a study on the architectural features of heritage buildings that have been converted into museums. These buildings are known to be climate responsive, and its building materials were properly selected to attenuate exterior conditions. Museum, on the other hand need to have a stable indoor climate in order to safeguard collections it housed. This practice is part of preventive conservation, an approach to prevent objects from deterioration. The characteristics of heritage buildings which were built to response with the climatic conditions may help to contribute a better indoor environment for the collections. The aim of this research is to undertake an investigative study exploring the heritage buildings which currently have been converted into museums to find its architectural features that able to control indoor climate passively which in turn can used in preventive conservation. A proper methodology was adopted in this dissertation to fulfill the objectives. The methodology includes reviewing related books, journals, working papers, and articles from internet. Case studies were also applied in this dissertation and were analyzed through physical observation. Two museums were chosen; the Army museum in Port Dickson and the National Textile Museum in Kuala Lumpur. This study showed that the buildings, occupied by those museums were designed to deal with climate passively and have features that able to regulate the temperature and relative humidity, which in turn can be utilized by the museums. It showed that converting the heritage building into a museum requires only minimum changes and alterations to the building. This in turn helps to preserve and maintain the authenticity and characteristics the building has. The result of this study can provide answers and examples of architectural features of heritage buildings that can be incorporated into the decision-making process for museum projects. The process also can be used to promote building design that able to control climate passively, without relying heavily on the HVAC mechanical system which in turn highlight energy efficiency and sustainability in museum design. Apart from that, this research could also act as a catalyst for future research on the standards and practice of museum and also on the adaptive re-use activities in Malaysia.